Working from home or back to the office? - The impact of the recent turbulence on office work - Grozdics, Anett Tímea; Girán, János; Uhrin, Anett; Balogh, Gábor; Cakó, Balázs; Cselik, Bence; Borsos, Ágnes (Marketing & Menedzsment, 2023)
THE AIMS OF THE PAPER Previous studies have shown that office spaces are priority areas for research. The shocks of recent years, such as the pandemic, have radically changed the lives of office workers in particular, so researchers consider research related to office spaces increasingly relevant. This research aims to present a systematic literature review (SLR) on the relationship between turbulent times working from home (WFH) during the pandemic and outline the possibility of WFH during the pandemic and that the workers will continue to work in the home office. METHODOLOGY The study uses the method of systematic literature review to achieve the research goal. The process provides an opportunity to transparently collect empirical studies on the given research question. The research took place between 2021-2022, with 54 relevant literature items being included for processing. MOST IMPORTANT RESULTS Our results showed that working from home was and remained an industry-specific option. The competition for talent has intensified in recent years. Employers can get the most out of them, reconstruct their operations and determine what can be monitored remotely. Our results also show that the time, energy and cost of commuting to work are the second most influential motivational factors. In this way, the costs of the employers can also be reduced since they can optimize their office space in connection with the new work organization, thereby reducing their rent and overhead costs. RECOMMENDATIONS The literature review outlined that by adapting and rethinking the experiences during the pandemic, many organizations can organize their work processes more efficiently in the future in accordance with health regulations. Thanks to the shift towards a knowledge-based economy and the spread of Industry 4.0, remote work can be one of the decisive tools for curbing climate change. Acknowledgement: The research project is conducted within the Biomedical Engineering Project of the Thematic Excellence Programme framework. An application for ethical approval for the research methods used in the research "Parameterised comfort in physical spaces" was submitted to the Scientific and Research Ethics Committee of the Health Sciences Council, which granted ethical approval.